Adam Smith and the Marquis de Condorcet. Did they really meet? - Pisanelli, Simona (Iberian Journal of the History of Economic Thought, 2015)
This article focuses on the alleged direct acquaintanceship between Condorcet and Adam Smith. Mistaken infor-mation about this issue was repeated many times in the literature of the late 1800s and 1900s. It is presumed that they met in France, during Smith’s journey there, chez Sophie de Grouchy. I will attempt to show that the meeting be-tween the two authors was not in fact arranged by Sophie de Grouchy, Condorcet’s wife, even though she was very interested in Smithian theories, especially about the category of “sympathy”, as confirmed by her French translation of the Theory of Moral Sentiments. My purpose is to demonstrate that Madame de Condorcet did never meet Smith and, as a result, she could not have introduced Condorcet to Smith. A greater degree of probability can be attributed to the version that indicates Turgot as the intermediary between Condorcet and Smith. In my opinion, not even this hypothesis is totally convincing, because neither Smith nor Condorcet ever talk about their meeting. Moreover, there is no evidence of correspondence between them.